Biological interpretation of the sporadic sputum smear-positive-culture-negative outcome for patients with tuberculosis undertaking treatments - Luo, Jingjing; Yu, Xia; Dong, Lingling; Huo, Fengmin; Ma, Yifeng; Liang, Qian; Shang, Yuanyuan; Huang, Hairong (Frontiers in Public Health, 2023)
Introduction The objective of the study was to identify the causes of smear-positive-culture-negative (S+/C–) outcomes of patients with tuberculosis during the treatment course. Methods A laboratory-based retrospective study was performed at the Beijing Chest Hospital in China. Within the study period, all patients with pulmonary tuberculosis (PTB) who undertook anti-TB treatments and yielded smear positive outcomes with simultaneous culture outcomes on sputa were considered. Patients were classified into three groups: (I) performed LJ medium culture only; (II) performed BACTEC MGIT960 liquid culture only; and (III) performed both LJ culture and MGIT960 culture. The S+/C– rates of each group were analyzed. The clinical medical records regarding patient category, follow-up bacteriologic examination data, and treatment response were investigated. Results In total, 1,200 eligible patients were enrolled, and the overall S+/C– rate was 17.5% (210/1,200). Group I had obviously higher S+/C– rate (37%) than group II (18.5%) and group III (9.5%). When solid and liquid cultures were considered independently, the S+/C– outcome was observed more frequently in the solid culture group than in the liquid culture group (30.4%, 345/1,135 vs. 11.5%, 100/873; p < 0.001, χ2 = 102.64). Among the 102 S+/C– patients who had follow-up cultures performed, 35 (34.3%) had positive culture outcomes. Whereas among the 67 patients with follow-up information for more than 3 months but without supportive bacteriological evidence, 45 (67.2%, 45/67) had unfavorable prognosis (including relapse and unimproved conditions), and only 22 (32.8%, 22/67) patients had improved conditions. Compared with new cases, retreated cases produced S+/C– outcomes more frequently and had more chances to be cultivated bacilli successfully afterward. Conclusions Among our patients, the sporadic smear positive and culture negative outcomes for sputa are more likely associated with the technical failures of culture than with dead bacilli, and this is especially noteworthy for LJ medium culture.